2016
DOI: 10.1002/ijc.30214
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent radiotherapy and intrathecal methotrexate for treating leptomeningeal metastasis from solid tumors with adverse prognostic factors: A prospective and single‐arm study

Abstract: The prognosis of leptomeningeal metastasis (LM) from solid tumors is extremely poor, especially for patients with adverse prognostic factors. In this phase II clinical trial, we evaluated the efficacy and safety of intrathecal chemotherapy (IC) combined with concomitant involved‐field radiotherapy (IF‐RT) for treating LM from solid tumors with adverse prognostic factors. Fifty‐nine patients with LM from various solid tumors were enrolled between May 2010 and December 2014. Concurrent therapy consisted of conco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(47 citation statements)
references
References 42 publications
1
45
1
Order By: Relevance
“…Radiation may also restore CSF flow and relieve hydrocephalus by reducing tumor bulk and, in doing so, facilitate the use of IT chemotherapy . In addition to the long‐term side effects of radiotherapy alone, there may also be an increased risk of late leukoencephalopathy when combined with other chemotherapeutic agents, such as intravenous or IT methotrexate . Radiation is unlikely to prolong survival based on retrospective studies in patients with breast and lung cancers, but it can result in rapid symptom improvement .…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Radiation may also restore CSF flow and relieve hydrocephalus by reducing tumor bulk and, in doing so, facilitate the use of IT chemotherapy . In addition to the long‐term side effects of radiotherapy alone, there may also be an increased risk of late leukoencephalopathy when combined with other chemotherapeutic agents, such as intravenous or IT methotrexate . Radiation is unlikely to prolong survival based on retrospective studies in patients with breast and lung cancers, but it can result in rapid symptom improvement .…”
Section: Treatmentmentioning
confidence: 99%
“…47 In addition to the long-term side effects of radiotherapy alone, there may also be an increased risk of late leukoencephalopathy when combined with other chemotherapeutic agents, such as intravenous or IT methotrexate. 35,[48][49][50][51][52] Radiation is unlikely to prolong survival based on retrospective studies in patients with breast and lung cancers, but it can result in rapid symptom improvement. 53,54 Eradication of tumor cells from the leptomeninges would require craniospinal irradiation, which carries significant potential CNS and systemic toxicities, including myelosuppression, that may compromise future cytotoxic chemotherapy options.…”
Section: Radiationmentioning
confidence: 99%
“…Before tyrosine kinase inhibitors (TKIs) and anti-angiogenesis drugs were used in NSCLC, the management of LMs relied on chemoradiotherapy but with great heterogeneity and outcomes were disappointing. 7,[10][11][12][13][14] The data from a retrospective study including 519 cases with LMs from solid tumors indicated MST was only 3 months with 10% of 1-year survival rate. 7 Even for patients treated with chemoradiotherapy, MST was just 5 months.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the most frequently used drugs, intrathecal administration of gemcitabine (85) or etoposide (86) has resulted in clinical activity in some case reports. Finally, a more recent prospective, single-arm study evaluated the efficacy and safety of intrathecal chemotherapy (methotrexate) combined with concomitant involved-field radiotherapy in 59 patients with LM from various solid tumors (42 lung cancers) and showed an encouraging efficacy (RR of 86.4% and median OS of 6.5 months), with acceptable toxicity (87). P r o s p e c t i v e d a t a o n t h e e f f i c a c y o f s y s t e m i c chemotherapy in the treatment of LC from NSCLC are lacking.…”
Section: Chemotherapy As Salvage Treatment For Progressive Bmsmentioning
confidence: 99%